The value of vulnerability: The transformative capacity of risky trust - Luigino Bruni; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
The "grammar of trust" is one the most explored loci in game theory and behavioural economics. However, still much needs to be understood about the nature of trust in non-enforceable, personalised interactions, in markets and within organizations. This experimental study aims at contributing to the understanding of new dimensions of trust by exploring how risky and vulnerable trust may foster a trustees behavioural change. It investigates trustees positive reciprocity when the intentional vulnerability of the trustor is both manifestly salient and dependent upon the trustees revealed type. The results support the transformative nature of risky trust by showing the capacity of vulnerable trust to generate more fairness and reciprocity in untrustworthy people.
Keywords: C72; C92; D01; 330; experiment; gift-exchange game; organization; trust; vulnerability